Effects of fermentation on the rheological characteristics of dough and the quality of steamed bread. Issue 10 (21st July 2019) - Yue, Qinghua; Liu, Chong; Li, Limin; Zheng, Xueling; Bian, Ke
Abstract: During the production of steamed bread, fermentation is a critical step to obtain a final product with the desired characteristics. The quality of the final steamed bread is significantly affected by the properties of the dough. This study investigated the effects of fermentation on the rheological properties, state of water, microstructure of the dough, and the quality of steamed bread. After fermentation, the steamed bread dough exhibited higher stickiness, and was more easily to break during uniaxial extension. Biaxial extension tests revealed a significant decrease in biaxial extensional viscosity from 110, 118 (0 min) to 11, 544 Pa·S (80 min) at the strain rate of 0.04/S. The properties of the dough matrix were closely related to the fermentation time and the quality of the steamed bread is significant affected by the fermentation time. The results is valuable to provide theoretical basis for steamed bread making under precise control. Practical applications: Fermentation is a key step in the production of steamed bread. This study (a) investigated the rheological properties of Chinese steamed bread dough during fermentation, including dough stickiness, uniaxial extensibility, and biaxial extension; (b) evaluated the effects of fermentation on the microstructure of fermented dough and steamed bread quality; and (c) investigated the relationship between the fermentation process and the quality of steamed bread. The information provided in this work will serve as the basis for further study on physical properties of fermented dough. The results is very valuable to provide theoretical basis for determining quality during the industrial production of steamed bread. This potentially leads to improved quality of steamed bread under precise control.